Lived Experiences of Education Graduates with Leadership Positions - Hibaya, Rey B.; Serohijos, Clent John S.; Caballeda, Velica A.; Gacasan, Anacleta A.; Baluyos, Genelyn R. (EduLine: Journal of Education and Learning Innovation, 2025)
School leaders play a critical role in shaping organizational culture and fostering a supportive environment for educators and students. The study delved into the lived experiences of education graduates with leadership positions during the second semester of the school year 2023-2024 in the public schools in one of the city divisions in Misamis Occidental. The study used a qualitative approach, and education graduates were chosen through purposive sampling. In-depth face-to-face interviews through a researcher-made interview guide were conducted. Data were analyzed using HyperResearch software following Moustakas's (1994) Data Analysis Framework. Results unveiled 12 themes: balancing personal, professional, and social responsibilities; implementing programs, policies, and activities; making effective decisions; personal, professional, and social motivations; dealing and adjusting with teachers, students, and school operations; witnessing teachers, students, and school activities succeed; exposure to diverse opportunities; deeper understanding of educational concepts; development of skills and abilities; development of effective leadership traits; personal fulfillment and gratification, and enhancement of teaching and learning process. School leaders navigate their experiences and foster development in education through strategic decision-making, adaptability, and a commitment to passion, driving transformative leadership that enhances personal, academic, and professional growth while fostering environments for success and recognition. Future researchers may consider exploring the strategies employed by school leaders to effectively manage the evolving demands, changes, and trends in 21st-century education.